Bismuth-based nanofiber photocatalytic material as well as preparation method and application thereof
By preparing bismuth-based nanofiber photocatalytic materials and utilizing electrospinning and staged calcination techniques, the problem of simultaneous treatment of organic pollutants and heavy metal ions in electroplating wastewater was solved, achieving efficient and stable photocatalytic effects and reducing treatment costs and the risk of secondary pollution.
Patent Information
- Application Number
- CN202511464418.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2026-01-02
AI Technical Summary
Existing technologies are insufficient to simultaneously and efficiently treat organic pollutants and heavy metal ions in electroplating wastewater. Traditional photocatalysts have low efficiency in utilizing visible light, and nanoparticle catalysts are difficult to recycle, leading to secondary pollution and high costs.
Using bismuth-based nanofiber photocatalytic materials, a three-dimensional nanofiber membrane was prepared by electrospinning technology. By combining vanadium, halogen or molybdenum elements to regulate the band structure, visible light response and redox dual-function catalytic activity were achieved. A stable nanofiber structure was formed by staged calcination.
It achieves efficient oxidation of organic pollutants and reduction of heavy metal ions under visible light. The material is easy to recycle, has high catalytic activity and stability, and reduces treatment costs and the risk of secondary pollution.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of photocatalytic materials, in particular to a bismuth-based nanofiber photocatalytic material and a preparation method and application thereof. BACKGROUND
[0002] Electroplating wastewater is a typical high-toxicity and difficult-to-treat industrial wastewater. It is complex in composition, containing not only high-toxicity heavy metal ions (such as chromium Cr(VI), copper Cu(II), nickel Ni(II), etc.), but also various high-concentration organic pollutants (such as dyes, surfactants, complexing agent EDTA, etc.). Therefore, it can easily pose a serious threat to the ecological environment and human health. Traditional physical and chemical treatment methods (such as chemical precipitation, adsorption, ion exchange) have problems such as secondary pollution, high operating cost, and difficulty in simultaneously treating multiple pollutants.
[0003] Photocatalytic technology, as a kind of advanced oxidation / reduction process driven by solar energy, has shown great potential in treating refractory organic pollutants. However, its application to actual electroplating wastewater treatment still faces many challenges. First, traditional wide-bandgap semiconductor photocatalysts (such as TiO2) mainly respond to ultraviolet light, and have low utilization efficiency for visible light, which accounts for most of the energy of sunlight, limiting their actual application performance. Second, electroplating wastewater is a typical composite pollution system, and single-function catalysts are difficult to achieve simultaneous efficient oxidation degradation of organic pollutants and reduction and fixation of heavy metal ions. If treated separately, the process is complex and the cost is high.
[0004] In order to overcome the above bottlenecks, researchers have made many explorations. On the one hand, by element doping (such as non-metallic doping) or constructing heterojunctions (such as bismuth-based semiconductors), visible light responsive photocatalytic materials are developed to improve the utilization rate of sunlight. On the other hand, by immobilizing the catalyst (such as loading on a carrier or making a thin film), the separation and recovery problem is solved. However, many existing technical solutions still have obvious shortcomings: either the catalytic activity and stability cannot be balanced; or only one type of pollutant can be preferentially treated, making it difficult to achieve one-material dual-effect synergistic purification.
[0005] Electrospinning technology provides an effective way to construct self-supporting three-dimensional nanofiber membrane materials. This structure has high specific surface area, abundant active sites and good structural stability, which is beneficial to mass transfer and light absorption, and facilitates separation and recovery. However, how to organically combine visible light response characteristics, oxidation-reduction dual functional catalytic activity and stable nanofiber structure through reasonable material design and controllable preparation process is still a key technical problem to be solved in the field of deep treatment of electroplating wastewater. SUMMARY
[0006] The application aims to provide a bismuth-based nanofiber photocatalytic material, a preparation method and application thereof, which has high catalytic activity, good stability and is easy to recycle and reuse.
[0007] To achieve the above-mentioned purpose, the application provides a preparation method of a bismuth-based nanofiber photocatalytic material, which specifically comprises the following steps: S1, preparation of a spinning precursor solution A high-molecular polymer carrier is dissolved in an organic solvent to obtain a polymer solution; a bismuth source and at least one vanadium source, halogen source or molybdenum source auxiliary source are added to the polymer solution and stirred uniformly to obtain a spinning precursor solution; S2, electrospinning The precursor solution obtained in step S1 is loaded into a syringe of an electrospinning device, and electrospinning is performed by setting spinning parameters, and a polymer nanofiber membrane is collected on a receiving device; S3, high-temperature calcination The polymer nanofiber membrane obtained in step S2 is subjected to stage-wise temperature calcination, the first stage removes the high-molecular polymer template, and the second stage crystallizes the inorganic crystal, and finally the bismuth-based nanofiber photocatalytic material is obtained.
[0008] Preferably, in step S1, the high-molecular polymer is polyvinylpyrrolidone or polyacrylonitrile; and the organic solvent is one of N,N-dimethylformamide, ethanol or N,N-dimethylacetamide.
[0009] Preferably, in step S1, the mass-volume concentration of the high-molecular polymer in the organic solvent is 0.08-0.15 g / mL.
[0010] Preferably, in step S1, the element molar ratio of the bismuth source and the auxiliary source is 1:0.5-2.0.
[0011] Preferably, in step S1, the bismuth source is one of bismuth nitrate pentahydrate, bismuth chloride and bismuth citrate; the vanadium source is one of ammonium metavanadate and vanadyl acetylacetonate; the halogen source is one of potassium iodide, potassium bromide and potassium chloride; and the molybdenum source is one of ammonium molybdate and sodium molybdate.
[0012] Preferably, in step S2, the spinning parameters are set as follows: the spinning voltage is 10-25 kV, the advancing rate is 0.5-2.0 mL / h, and the receiving distance is 10-20 cm.
[0013] Preferably, in step S3, the first-stage calcination temperature is 250-350℃, and the calcination time is 1-3h; the second-stage calcination temperature is 400-550℃, and the calcination time is 2-4h.
[0014] The application further provides a bismuth-based nanofiber photocatalytic material prepared by the preparation method.
[0015] The application further provides application of the bismuth-based nanofiber photocatalytic material in synchronous removal of organic pollutants and heavy metal ions in electroplating wastewater.
[0016] Preferably, the organic pollutants are one or more of rhodamine B, methyl orange or ethylenediaminetetraacetic acid. The heavy metal ions are one or more of Cr(VI), Cu(II) or Ni(II).
[0017] The application uses bismuth (Bi) as a matrix, uses the lone pair electron effect of bismuth to construct a visible light response foundation with a narrow band gap and a unique layered structure, and then introduces vanadium (V), halogen (I / Br / Cl) or molybdenum (Mo) elements, the key role of which is to further regulate the energy band structure through atomic-level hybridization, the p orbital of halogen significantly lifting the valence band top to enhance visible light absorption, the d orbital of vanadium forming a suitable reduction potential conduction band bottom, and the introduction of molybdenum potentially forming a heterojunction to promote charge separation. The chemical bonding of these elements with bismuth cooperatively endows the material with the intrinsic ability to efficiently capture visible light and generate electron-hole pairs at the atomic scale. Through the above-mentioned cooperation between elements, electrospinning and high-temperature calcination technology, a visible light response type photocatalytic material capable of efficiently driving a synergistic oxidation-reduction reaction is prepared, enabling the material to simultaneously drive efficient reactions of hole oxidation of organic matter and electron reduction of heavy metal ions, and realizing the "one material with double effects" synergistic treatment of complex electroplating wastewater.
[0018] Specifically, when visible light irradiates the bismuth-based photocatalytic material, the electrons on the valence band will be excited to jump to the conduction band, leaving holes on the valence band at the same time, and the holes themselves have strong oxidizing properties and can react with water molecules to generate hydroxyl radicals. These strong oxidizing substances can non-selectively oxidize and decompose organic pollutants in electroplating wastewater into small molecular inorganic substances such as CO2 and H2O. The electrons jumping to the conduction band have strong reducing properties and can reduce the heavy metal ions with high toxicity and high solubility into low-toxicity or easily precipitated forms. For example, Cr(VI) with high toxicity is reduced to low-toxicity Cr(III), which is easy to form Cr(OH)3 precipitate; Cu(II) is easily reduced to Cu 0 The elemental deposition on the surface of the material. Therefore, the synergistic removal of organic pollutants and heavy metal ions in electroplating wastewater can be achieved.
[0019] The electrospinning is to stretch the precursor solution containing high polymer, bismuth source and auxiliary source (vanadium source, halogen source or molybdenum source) into nanofiber through high-voltage electrostatic field, which realizes the uniform distribution of the precursor and the controllable formation of the nanofiber structure, provides a high specific surface area template for subsequent calcination, and provides abundant adsorption sites and photocatalytic reaction sites for pollutants. The fiber structure can make the light reflect and scatter multiple times inside, thereby improving the utilization rate of light energy. The high polymer as a carrier ensures the full dispersion of the bismuth source and the auxiliary source in the solution, avoids phase separation, and makes the element distribution of the final product uniform. In the process of high-temperature calcination in stages, the first stage (250-350 DEG C) calcination can slowly remove the high polymer, avoid the collapse of the fiber structure, and leave the inorganic precursor skeleton. The second stage (400-550 DEG C) calcination can promote the crystallization of bismuth compounds (such as BiVO4, BiOI and Bi2MoO6), and form a crystal phase with photocatalytic activity. The staged temperature rise controls the crystal growth rate and maintains the morphology of the nanofiber.
[0020] Therefore, the application provides a bismuth-based nanofiber photocatalytic material and a preparation method and application thereof. First, in the material design, the traditional tungsten source is abandoned, and the vanadium source, halogen source or molybdenum source is innovatively used to compound with the bismuth-based material, which effectively controls the energy band structure of the material, so that the material has excellent visible light response characteristics, thereby widening the light energy utilization range and significantly improving the separation efficiency of the photo-generated electron-hole pairs. Second, in the material structure, the electrospinning technology is used to successfully construct a three-dimensional nanofiber network. This structure not only provides a large specific surface area and abundant reaction sites to promote the mass transfer and adsorption of pollutants, but also enhances the light capture ability through multiple reflection and scattering of light. At the same time, its self-supporting membrane form fundamentally solves the bottleneck problem of easy agglomeration and difficult recycling of nanometer powder catalyst, and is convenient for separation and recycling from the treated water. The prepared material has a dual-function synergistic purification ability when treating complex electroplating wastewater. Under light, the photo-generated holes and derived active oxygen species can efficiently oxidize and decompose organic pollutants, while the photo-generated electrons can simultaneously reduce high-valence heavy metal ions to low-toxicity form, which can deeply purify the electroplating wastewater, and the solid nanofiber skeleton ensures excellent cycle stability, and can still maintain high catalytic activity after multiple uses. In addition, the entire preparation process is simple, controllable and reproducible, and has significant industrial application potential.
[0021] The technical solutions of the application will be further described in detail through examples. DETAILED DESCRIPTION
[0022] The application will be further described in connection with the specific embodiments. It should be understood that these embodiments are only used to illustrate but not to limit the scope of the application, and any changes, modifications, substitutions, combinations, simplifications made without departing from the spirit and principles of the application shall be equivalent replacements and shall fall within the scope of the application. In addition, it should be understood that after reading the content of the application, those skilled in the art can make various modifications or modifications to the application, and these equivalent forms also fall within the scope defined by the claims of the application and belong to the protection scope of the application.
[0023] Reference herein to "embodiment" means that a particular feature, structure, or characteristic described in connection with the embodiment can be included in at least one embodiment of the application. The term "embodiment" appearing in various positions in the specification does not necessarily refer to the same embodiment, nor does it particularly limit its independence or association with other embodiments. In principle, in this application, as long as there is no technical contradiction or conflict, the technical features mentioned in each embodiment can be combined in any way to form a corresponding implementable technical solution.
[0024] Unless otherwise defined, the meanings of the technical terms used herein are the same as those commonly understood by those skilled in the art to which the application belongs; the use of related terms herein is only for the purpose of describing specific embodiments and is not intended to limit the application.
[0025] Unless otherwise specified, the reagents, instruments, and equipment used in the application are conventional reagents, instruments, and equipment used by those skilled in the art.
[0026] Embodiment 1 The embodiment provides a preparation method of a bismuth-based nanofiber photocatalytic material, and specifically comprises the following steps: S1, preparation of a spinning precursor solution Dissolve 1.0 g of polyvinylpyrrolidone (PVP) in 10 mL of N,N-dimethylformamide, magnetically stir for 6 hours to form a uniform polymer solution, add 2.42 g of bismuth nitrate pentahydrate and 0.585 g of ammonium metavanadate to the above solution, and continue to stir for 12 hours to obtain a completely dissolved and uniformly dispersed spinning precursor solution.
[0027] S2, electrospinning The spinning precursor solution is loaded into a syringe, a stainless steel needle is installed, and the electrospinning parameters are set as follows: spinning voltage 15 kV, pushing rate 1.0 mL / h, and receiving distance 15 cm. Start the electrospinning device and continue spinning for 8 h to collect a uniform and continuous BiVO4 / PVP polymer nanofiber membrane on the aluminum foil receiving device.
[0028] S3, high-temperature calcination The polymer nanofiber membrane is peeled off from the aluminum foil, cut into small pieces and placed in a muffle furnace for programmed temperature calcination. First, the temperature is raised to 300°C at a rate of 2°C / min (first stage), and calcination is maintained for 2h to remove the PVP template. Then, the temperature is continuously raised to 500°C at a rate of 2°C / min (second stage), and calcination is maintained for 3h to promote BiVO4 crystal crystallization. After calcination, the temperature is naturally cooled to room temperature to obtain the BiVO4 nanofiber photocatalytic material.
[0029] Example 2 The present embodiment provides a preparation method of a bismuth-based nanofiber photocatalytic material, which specifically comprises the following steps: S1, preparation of a spinning precursor solution 1.0g of polyacrylonitrile (PAN) is dissolved in 10mL of N,N-dimethylformamide, and magnetic stirring is performed for 5 hours to form a uniform polymer solution. 2.42g of bismuth nitrate pentahydrate and 0.83g of potassium iodide are added to the above solution, and stirring is continued for 12 hours to obtain a completely dissolved and uniformly dispersed spinning precursor solution.
[0030] S2, electrospinning The spinning precursor solution is loaded into a syringe, a stainless steel needle is installed, and the electrospinning parameters are set as follows: spinning voltage 18kV, pushing rate 1.2mL / h, and receiving distance 12cm. The electrospinning device is started, and spinning is continuously performed for 8h to collect a uniform and continuous BiOI / PAN polymer nanofiber membrane on the aluminum foil receiving device.
[0031] S3, high-temperature calcination The polymer nanofiber membrane is peeled off from the aluminum foil, cut into small pieces and placed in a muffle furnace for programmed temperature calcination. First, the temperature is raised to 280°C at a rate of 2°C / min (first stage), and calcination is maintained for 2.5h to remove the PVP template. Then, the temperature is continuously raised to 450°C at a rate of 2°C / min (second stage), and calcination is maintained for 3.5h to promote BiOI crystal crystallization. After calcination, the temperature is naturally cooled to room temperature to obtain the BiOI nanofiber photocatalytic material.
[0032] Example 3 The present embodiment provides a preparation method of a bismuth-based nanofiber photocatalytic material, which specifically comprises the following steps: S1, preparation of a spinning precursor solution 1.0g of polyvinylpyrrolidone (PVP) is dissolved in 10mL of N,N-dimethylformamide, and magnetic stirring is performed for 6 hours to form a uniform polymer solution. 2.42g of bismuth nitrate pentahydrate and 0.484g of ammonium molybdate are added to the above solution, and stirring is continued for 12 hours to obtain a completely dissolved and uniformly dispersed spinning precursor solution.
[0033] S2, electrospinning The spinning precursor solution was loaded into a syringe, a stainless steel needle was installed, and the electrospinning parameters were set as follows: spinning voltage 16 kV, pushing rate 1.0 mL / h, and receiving distance 16 cm. The electrospinning device was started, and spinning was continued for 8 h. A uniform and continuous Bi2MoO6 / PVP polymer nanofiber membrane was collected on the aluminum foil receiving device.
[0034] S3, high-temperature calcination The polymer nanofiber membrane was peeled off from the aluminum foil, cut into small pieces, and placed in a muffle furnace for programmed temperature rising calcination. First, the temperature was raised to 320°C at a rate of 2°C / min (first stage), and the PVP template was removed by calcination for 1.5 h. Then, the temperature was continuously raised to 520°C at a rate of 2°C / min (second stage), and the Bi2MoO6 crystal was crystallized by calcination for 3 h. After calcination, the sample was naturally cooled to room temperature to obtain the Bi2MoO6 nanofiber photocatalytic material.
[0035] Example 4 The present embodiment provides a preparation method of a bismuth-based nanofiber photocatalytic material, which specifically comprises the following steps: S1, preparation of a spinning precursor solution 1.0 g of polyvinylpyrrolidone (PVP) was dissolved in 10 mL of N,N-dimethylformamide, and magnetic stirring was performed for 6 hours to form a uniform polymer solution. 2.42 g of bismuth nitrate pentahydrate, 0.357 g of potassium bromide, and 0.35 g of ammonium molybdate were added to the above polymer solution, and stirring was continued for 12 hours to obtain a spinning precursor solution that was completely dissolved and uniformly dispersed.
[0036] S2, electrospinning The spinning precursor solution was loaded into a syringe, a stainless steel needle was installed, and the electrospinning parameters were set as follows: spinning voltage 17 kV, pushing rate 1.1 mL / h, and receiving distance 14 cm. The electrospinning device was started, and spinning was continued for 8 h. A uniform and continuous BiBrO-Bi2MoO6 / PVP polymer nanofiber membrane was collected on the aluminum foil receiving device.
[0037] S3, high-temperature calcination The polymer nanofiber membrane was peeled off from the aluminum foil, cut into small pieces, and placed in a muffle furnace for programmed temperature rising calcination. First, the temperature was raised to 310°C at a rate of 2°C / min (first stage), and the PVP template was removed by calcination for 2 h. Then, the temperature was continuously raised to 480°C at a rate of 2°C / min (second stage), and the BiBrO-Bi2MoO6 composite oxide crystal was crystallized by calcination for 3 h. After calcination, the sample was naturally cooled to room temperature to obtain the BiBrO-Bi2MoO6 composite nanofiber photocatalytic material.
[0038] Comparative Example 1 The only difference between this comparative example and Example 1 is that only 2.42g of bismuth nitrate pentahydrate was added to the polymer solution. Everything else was the same as in Example 1 and will not be repeated here. Pure Bi2O3 nanofibers were obtained.
[0039] Comparative Example 2 The only difference between this comparative example and Example 1 is that the first stage of high-temperature calcination is 400°C for 2 hours, and the second stage is 600°C for 3 hours. All other aspects are the same as in Example 1 and will not be repeated here.
[0040] The photocatalytic performance and cycle stability of the materials prepared in the above embodiments and comparative examples were tested. The test methods are as follows: Photocatalytic performance test: Multiple groups of electroplating wastewater containing different types of organic pollutants and heavy metal ions were simulated. 0.1g of photocatalytic material was added to 100mL of wastewater from each group, and the mixture was irradiated under visible light (xenon lamp, 500W) for 2 hours. The concentration of organic pollutants was measured using a UV-Vis spectrophotometer, and the concentration of heavy metal ions was measured using the diphenylcarbazide method. The degradation rate and reduction rate were calculated. The electroplating wastewater in the first group contained Rhodamine B (RhB, 10 mg / L) and Cr(VI) (10 mg / L); the electroplating wastewater in the second group contained methyl orange (MO, 10 mg / L) and Cu(II) (10 mg / L); the electroplating wastewater in the third group contained ethylenediaminetetraacetic acid (EDTA, 10 mg / L) and Ni(II) (10 mg / L); and the electroplating wastewater in the fourth group contained Rhodamine B (RhB, 5 mg / L), ethylenediaminetetraacetic acid (EDTA, 5 mg / L), and Cr(VI) (10 mg / L). The test results are shown in Tables 1-4.
[0041] Cyclic stability test: The photocatalyst materials from the first and second groups of electroplating wastewater were recovered, washed, dried, and reused 5 times. The activity retention rate of the catalyst after the 5th cycle was calculated (the activity of the first cycle was taken as 100% baseline). The results are shown in Tables 5 and 6.
[0042] Table 1. Data on the simultaneous removal of RhB and Cr(VI)
[0043] Table 2. Simultaneous removal data of MO and Cu(II)
[0044] Table 3. Data on the simultaneous removal of EDTA and Ni(II)
[0045] Table 4. Simultaneous Removal Data of RhB, EDTA, and Cr(VI)
[0046] From the data in Table 1-Table 4, it can be seen that the bismuth-based nanofiber photocatalytic material prepared in the embodiments of the present application has excellent simultaneous purification ability in various pollutant systems. The degradation rate of RhB and MO is basically 90%-96%, the degradation rate of EDTA is 80%-90%, the reduction rate of Cr(VI), Cu(II), and Ni(II) is 70%-92%, even for the mixed pollutant system of RhB+EDTA+Cr(VI), it still maintains high degradation efficiency and removal efficiency; the performance of the materials of Comparative Example 1 and Comparative Example 2 is significantly attenuated, the degradation rate of organic pollutants is only 55%-72%, and the reduction rate of heavy metals is only 45%-62%, which shows that the introduction of vanadium / halogen / molybdenum auxiliary source to regulate the energy band structure, the combination of electrospinning technology and the design of reasonable phased and reasonable calcination parameter design are the key to ensure that the material realizes efficient oxidation of organic matter and reduction of heavy metals.
[0047] Table 5: Photocatalytic material recycling stability data for recycling the first group of electroplating wastewater
[0048] Table 6: Photocatalytic material recycling stability data for recycling the second group of electroplating wastewater
[0049] From the data in Table 5-Table 6, it can be seen that the bismuth-based nanofiber photocatalytic material prepared in the embodiments of the present application has excellent recycling stability, and after 5 cycles, the activity retention rate is still maintained at 92%-96.8%, while the recycling stability of Comparative Example 1 and Comparative Example 2 is significantly poorer, and the activity retention rate of the 5th cycle is only 70.8%-83.4%. This shows that the nanofiber network structure prepared in the present application has excellent mechanical strength and anti-inactivation ability, and has long-term effectiveness and reusability in practical application.
[0050] Finally, it should be noted that: the above embodiments are only used to illustrate the technical solutions of the present application but not to limit them, although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can still be modified or replaced by equivalents, and these modifications or equivalent replacements cannot make the modified technical solutions deviate from the spirit and scope of the technical solutions of the present application.
Claims
1. A method for preparing a bismuth-based nanofiber photocatalytic material, characterized in that, Specifically, the following steps are included: S1. Preparation of spinning precursor solution A polymer carrier is dissolved in an organic solvent and stirred to obtain a polymer solution; a bismuth source and at least one vanadium source, halogen source or molybdenum source auxiliary source are added to the polymer solution and stirred evenly to obtain a spinning precursor solution; S2, electrospinning The precursor solution obtained in step S1 is loaded into the syringe of the electrospinning device, the spinning parameters are set to perform electrospinning, and the polymer nanofiber membrane is collected on the receiving device. S3, High-temperature calcination The polymer nanofiber membrane obtained in step S2 is subjected to staged heating and calcination. The first stage removes the polymer template, and the second stage crystallizes the inorganic crystals, ultimately producing a bismuth-based nanofiber photocatalytic material.
2. The method for preparing a bismuth-based nanofiber photocatalytic material according to claim 1, characterized in that: In step S1, the polymer is polyvinylpyrrolidone or polyacrylonitrile; the organic solvent is one of N,N-dimethylformamide, ethanol or N,N-dimethylacetamide.
3. The method for preparing a bismuth-based nanofiber photocatalytic material according to claim 1, characterized in that: In step S1, the mass-volume concentration of the polymer in the organic solvent is 0.08-0.15 g / mL.
4. The method for preparing a bismuth-based nanofiber photocatalytic material according to claim 1, characterized in that: In step S1, the molar ratio of the bismuth source and the auxiliary source is 1:0.5-2.
0.
5. The method for preparing a bismuth-based nanofiber photocatalytic material according to claim 1, characterized in that, In step S1, the bismuth source is one of bismuth nitrate pentahydrate, bismuth chloride, or bismuth citrate; the vanadium source is one of ammonium metavanadate or acetylacetonate vanadium oxide; the halogen source is one of potassium iodide, potassium bromide, or potassium chloride; and the molybdenum source is one of ammonium molybdate or sodium molybdate.
6. The method for preparing a bismuth-based nanofiber photocatalytic material according to claim 1, characterized in that, In step S2, the spinning parameters are set as follows: spinning voltage is 10-25kV, feed rate is 0.5-2.0mL / h, and receiving distance is 10-20cm.
7. The method for preparing a bismuth-based nanofiber photocatalytic material according to claim 1, characterized in that: In step S3, the calcination temperature in the first stage is 250-350℃ and the calcination time is 1-3h; the calcination temperature in the second stage is 400-550℃ and the calcination time is 2-4h.
8. A bismuth-based nanofiber photocatalytic material, characterized in that: The photocatalytic material is prepared by the preparation method described in any one of claims 1-7.
9. The application of the bismuth-based nanofiber photocatalytic material as described in claim 8, characterized in that: The photocatalytic material is used to simultaneously remove organic pollutants and heavy metal ions from electroplating wastewater.
10. The application of the bismuth-based nanofiber photocatalytic material according to claim 9, characterized in that: The organic pollutant is one or more of Rhodamine B, methyl orange, or ethylenediaminetetraacetic acid; The heavy metal ions are one or more of Cr(VI), Cu(II), or Ni(II).
